Civil society and democracy in post-apartheid South Africa : the Treatment Action Campaign, government and the politics of HIV/AIDS - Neocosmos, Michael (University of Pretoria, 2013)
Mini Dissertation (MSocSci (Social Research))--University of Pretoria, 2005.